Housing Inequalities and Housing Provision for the Youth in Lithuania - Brazienė, Rūta; Okunevičiūtė Neverauskienė, Laima; Pocius, Arūnas; Vyšniauskienė, Sonata; Krauledaitė, Justina (Calitatea Vieții, 2024)
This paper discusses housing inequalities and housing provision for the youth (aged 18-35) in Lithuania. The study’s theoretical background is based on housing inequalities and housing provision (affordability, accessibility, etc.). 1 209 young people aged 18-35 participated in the study. According to the survey data in this article, the subjective assessment of young people’s housing (households of young people) covers several highly interrelated aspects: housing provision, housing autonomy, and housing differentiation by the income of youth in Lithuania. The research revealed that housing provision for the youth has become more complicated during the last decade. There is a lack of opportunities (and alternatives) for young people to purchase or rent suitable housing, and there are difficulties in becoming independent from parents/ guardians. Housing market instability and constantly rising housing (and real estate) prices limit accessibility to decent-quality housing for the youth. The scientific research is funded by the Lithuanian Science Council researcher’s group’s Project ‘Socio-economic Factors of Youth Life Chances Differentiation in Lithuania’ (Reg. No. S-MIP-22-42, contract date 18.03.2022).